"Justification by Faith": Richard Baxter's Influence upon John Wesley - Cunningham, Joseph William (The Asbury journal, 2012)
Correction In our Spring 2009 issue we published an essay, "'Justification by Faith": Richard Baxters Influence upon John Wesley." Due to an editing error, the essay was mistakenly attributed to Floyd T. Cunningham, president of Asia Pacific Nazarene Theological Seminary. We apologize to Dr. Cunningham for the inconveniences this mistake has caused. We also apologize to Dr. Joseph W Curmingham of Eureka College who is the correct author of the essay. In order to emphasize this correct attribution, we are republishing the essay in this issue with Dr. Joseph W Cunningham listed as the author.